Determination of Wound Healing Potential of Pharmaceutical Formulations (Gel and Paste) Prepared by Using Sea Water Snail - Pawar, Deepak P.; Shamkuwar, Prashant B. (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: Marine species have long been valued as both nutritious foods for human diets and as a good source of medicinal chemicals. Purpose: The present work aimed to investigate wound healing potential of prepared gel and paste formulation. Materials and Methods: The work involved the preparation of extracts, preparation of formulation using extract and shells of Tibia curta sea water snail and determination of action against wound healing. Sea water snail extract was utilised to make Gels with varying compositions (G1-G9), and snail shells were used to make Paste (P1-P6). The gel and paste were evaluated based on different parameters. Results: The formulations with a neutral pH and excellent spreadability (G7 and P1) were chosen for further wound healing studies (since neutral pH does not cause irritancy and improved spreadability results in increased medication effectiveness). The extract, as well as both formulations, were used to treat excise wounds. Conclusion: The reduction in skin thickness reveals that formulations formulated using snail extract and shell were more efficient than simple snail extract.
Keywords: Shell; Mollusca; Gel; Paste; Wound healing